Glypican 3-targeted chimeric antigen receptor T cells secreting TROP2-directed bispecific T cell engagers exhibit potent efficacy against lung squamous cell carcinoma - Ruan, Lianjie; Lin, Liming; Lin, Dekai; Zhang, Haiqing; Weng, Suiyan; Lin, Mengqing (Frontiers in Immunology, 2026)
BackgroundChimeric antigen receptor T cell (CAR-T) therapy faces multiple challenges in solid tumors, especially the heterogeneity of tumor antigens. Glypican-3 (GPC3) and trophoblast cell-surface antigen 2 (TROP2) are highly expressed antigens in lung squamous cell carcinoma (LUSC) for development of dual-targeted therapy. The absence of GPC3 in any normal tissues of adults makes it an ideal target for CAR-T therapy. However, TROP2 is expressed in the epithelial cells of various normal tissues and thus is not acceptable for direct design of CAR-T therapy due to the high risk of “on-target off-tumor” effects. Here we developed a dual-targeted LUSC therapy featuring a GPC3-targeted CAR-T cell secreting TROP2-directed bispecific T cell engagers (GPC3 CAR-T. TROP2 BiTE), and verified the antitumor activity in vitro and in vivo, respectively.MethodsImmunohistochemistry (IHC) was used to confirm the expression of GPC3 and TROP2 in LUSC and normal tissues. CAR-T cells were produced through lentiviral transduction of CAR genes. Real-time cytotoxicity assay (RTCA) was used to assess the cytotoxic effect of CAR-T cells on LUSC cells. Flow cytometry was utilized to examine the CAR-T cell phenotype, exhaustion and activation. Enzyme-linked immunosorbent assay (ELISA) was performed to detect the release of cytokines. To evaluate the activity of CAR-T cells in vivo, tumor-bearing immunodeficient mice were given a single intravenous injection of CAR-T cells, and the tumor burden and CAR-T cell expansion were regularly monitored.ResultsGPC3 was overexpressed in 70% of LUSC tissues, while negatively expressed in all normal tissues. Positive expression of TROP2 was observed in all LUSC tissues and also in many normal tissues. Compared with GPC3 CAR-T and TROP2 CAR-T, GPC3 CAR-T. TROP2 BiTE exhibited cytotoxicity to both GPC3+ and TROP2+ LUSC cells, and thereby showed faster killing and durable antitumor effect against LUSC cells with heterogenous expression of GPC3 and TROP2. In tumor-bearing mice, GPC3 CAR-T. TROP2 BiTE showed strong ability to eliminate tumors.ConclusionsThis study demonstrated that GPC3 CAR-T. TROP2 BiTE was a potent therapy for LUSC and provided a strategy for overcoming the antigen heterogeneity in solid tumors.